Protoperidinium bergh (Dinophyceae) of the National Park Sistema Arrecifal Veracruzano, Gulf of Mexico, with a key for identification - Okolodkov, Yuri B. (Instituto de Ecología, A.C., 2008)
The morphology of 46 species of Protoperidinium was studied based on 510 phytoplankton net samples taken from May 2005 through February 2007 at 7 stations in the northwestern part of the National Park Sistema Arrecifal Veracruzano, southern Gulf of Mexico. Forty-three species are represented by vegetative cells and three species only by cysts (P. oblongum, P. cf. stellatum and P. subinerme). Descriptions with an emphasis on the first apical and the second intercalary plates and synonymy are given for each species. Cell size variation, the mean and the standard deviation of three or four measurements are given for most species. The hypothecal pore in the first postcingular plate, a stable taxonomic feature, was observed only in P. solidicorne, P. pellucidum, P. ovum, P. sp. E meta-hexa and P. cf. hirobis; the position of the pore is also a conservative characteristic. Twentyfive species are provided with affinities and taxonomic, nomenclatural or biogeographic comments. A dichotomous key for identification of all the species found is presented, and species are illustrated with light microscope photographs. A new combination is proposed: Protoperidinium persicum (J. Schill.) Okolodkov comb. nov. Fifteen species are new records for the Gulf of Mexico, and about 25 species for the state of Veracruz.